Factors Influencing the Performance Accountability of Government Agencies, Literature Review - Pristy Wulandari; Putri Aditya Lestari; Putri Septiana Br. Sigalingging; Riandi Syahputra; Galih Supraja (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to analyze the factors that influence the performance accountability of government agencies through a literature review. Based on the results of the study, it was found that the implementation of performance-based budgeting, regional financial management information systems, clarity of budget targets, understanding of accounting, compliance with regulations, and accounting control are the main variables that influence performance accountability. The results of the study indicate that the implementation of performance-based budgeting makes a significant contribution to accountability, especially if supported by appropriate planning, implementation, and reporting. Clarity of budget targets plays an important role in facilitating the accountability process, while understanding of accounting and compliance with regulations strengthen transparency and accountability. An effective financial management information system also has a positive impact, although the implementation of the regional government accounting system shows varying results. These findings underline the importance of planned financial management, consistent implementation, and transparent reporting to achieve optimal performance accountability. This study contributes to improving good governance by emphasizing strategic factors that need to be considered by government agencies